Asymmetric viability in reciprocal crosses of zebrafish Danio rerio and pearl danio Danio albolineatus. Issue 1 (6th October 2021) - Delomas, Thomas A.; Dabrowski, Konrad
Abstract: Interspecies hybrids have long been studied to further understanding of speciation. Reciprocal crosses sometimes have asymmetric viability, a phenomenon termed 'Darwin's corollary to Haldane's rule'. It has been proposed that this asymmetry is caused by Dobzhansky–Muller incompatibilities between nuclear genes and cytoplasmic factors ( e.g ., maternal transcripts, mitochondrial genome). The molecular basis of this hypothesis has received little empirical investigation, presumably due to the lack of an appropriate model system. We report a case of extreme asymmetry in viability between reciprocal hybrids of zebrafish Danio rerio and pearl danio Danio albolineatus . Hybrids from D. rerio females ×  D. albolineatus males ( n  = 4 crosses) were viable, with 83.2 ± 9.6% surviving from fertilization to 5 days post‐fertilization (dpf) and 80.1 ± 14.4% surviving from 5 to 21 dpf. Hybrids from D. albolineatus females ×  D. rerio males ( n  = 6 crosses) were inviable after embryonic development. These hybrids developed pericardial oedema at 1 dpf and only 37.2 ± 18.0% survived from fertilization to 5 dpf. Of the 595 larvae alive at 5 dpf, only one juvenile with stunted growth survived to 21 dpf. We propose that given the resources available for the D. rerio model system and the strong asymmetry in viability between reciprocal crosses, these hybrids will allow investigation of the molecular basis for Darwin's corollary to Haldane's rule.